Removal Efficiency, Adsorption Kinetics and Isotherms of Phenolic Compounds from Aqueous Solution Using Rice Bran Ash - Gholizadeh, Abdolmajid; Kermani, Majid; Gholami, Mitra; Farzadkia, Mahdi; Yaghmaeian, Kamyar (Asian Journal of Chemistry, 2013)
In the present study, a porous rice bran ash powder was synthesized and tested for the removal of phenolic compounds from aqueous solution. The size of the rice bran ash particles was 14.49 nm, with a BET surface area of 50.14 m2g-1. Adsorption of phenol, 2-chlorophenol and 4-chlorophenol was conducted at various contact times, solution pHs, adsorbate concentrations and rice bran ash dosages in a batch reactor. Batch kinetic studies showed that an equilibration within 240 min could be achieved at pH as low as 5.0 ± 0.2 for the adsorption of 50 mg L-1 phenolic compounds concentration. Removal efficiency of 2-chlorophenol was lower than phenol and 4-chlorophenol. The phenol, 2-chlorophenol and 4-chlorophenol maximum removal efficiency was observed at an initial pH of 5 ± 0.2. Also the maximum predicted adsorption capacities were 4.6332, 3.6749 and 4.3060 mg g-1 for phenol, 2-chlorophenol and 4-chlorophenol, respectively. The capacity of phenol, 2-chlorophenol and 4-chlorophenol adsorption at equilibrium increased with the increase of initial concentration (50-400 mg L-1) and decreased with the increase of adsorbent dosage (2.5-10 g L-1). The isotherm evaluations revealed that the equilibrium data for 2-chlorophenol and 4-chlorophenol could be fitted with the Freundlich model, whereas the equilibrium data for phenol fitted with Langmuir model best. In addition, the adsorption kinetic data were found fit the test results well based on a pseudo-second-order rate for selected phenolic compounds.